Agroforestry Practices for Sustainable Intensification, Food Security and Climate Adaptation in Dry Areas: Challenges, Applications, and Examples - Idoudi, Zied; Frija, Aymen; Ouled Belgacem, Azaiez; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
Oral presentation on Agroforestry Practices for Sustainable Intensification, Food Security, and Climate Adaptation in Dry Areas: Challenges, Applications, and Examples – delivered on August 28th. This communication occurred during the 6th General Assembly of the IOFS in Tunis, Tunisia, as part of the Regional Conference on Resilient Agriculture in IOFS Member States, focusing on Climate Adaptation and Food Security (28 August 2023 / 04-12-13 September 2023).